Characterization of antimicrobial resistance genes in Haemophilus parasuis isolated from pigs in China - Zhao, Yongda; Guo, Lili; Li, Jie; Huang, Xianhui; Fang, Binghu (PeerJ, 2018)
Background Haemophilus parasuis is a common porcine respiratory pathogen that causes high rates of morbidity and mortality in farmed swine. We performed a molecular characterization of antimicrobial resistance genes harbored by H. parasuis from pig farms in China. Methods We screened 143 H. parasuis isolates for antimicrobial susceptibility against six fluoroquinolone antibiotics testing by the broth microdilution method, and the presence of 64 antimicrobial resistance genes by PCR amplification and DNA sequence analysis. We determined quinolone resistance determining region mutations of DNA gyrase (gyrA and gyrB) and topoisomerase IV (parC and parE). The genetic relatedness among the strains was analyzed by pulsed-field gel electrophoresis. Results Susceptibility test showed that all isolates were low resistance to lomefloxacin (28.67%), levofloxacin (20.28%), norfloxacin (22.38%), ciprofloxacin (23.78%), however, high resistance levels were found to nalidixic acid (82.52%) and enrofloxacin (55.94%). In addition, we found 14 antimicrobial resistance genes were present in these isolates, including blaTEM-1, blaROB-1, ermB, ermA, flor, catl, tetB, tetC, rmtB, rmtD, aadA1, aac(3′)-llc, sul1, and sul2 genes. Interestingly, one isolate carried five antibiotic resistance genes (tetB, tetC, flor, rmtB, sul1). The genes tetB, rmtB, and flor were the most prevalent resistance genes in H. parasuis in China. Alterations in the gyrA gene (S83F/Y, D87Y/N/H/G) were detected in 81% of the strains and parC mutations were often accompanied by a gyrA mutation. Pulsed-field gel electrophoresis typing revealed 51 unique patterns in the isolates carrying high-level antibiotic resistance genes, indicating considerable genetic diversity and suggesting that the genes were spread horizontally. Discussion The current study demonstrated that the high antibiotic resistance of H. parasuis in piglets is a combination of transferable antibiotic resistance genes and multiple target gene mutations. These data provide novel insights for the better understanding of the prevalence and epidemiology of antimicrobial resistance in H. parasuis.
Keywords: Antimicrobial resistance genes; QRDR; Haemophilus parasuis; PRGE